2009
DOI: 10.1099/vir.0.016691-0
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in receptor-binding properties of swine influenza viruses of the H1 subtype after isolation in embryonated chicken eggs

Abstract: Alterations of the receptor-binding properties of swine influenza A viruses (SIVs) during their isolation in embryonated chicken eggs have not been well studied. In this study, the receptorbinding properties of classical H1 SIVs isolated solely in eggs or Madin-Darby canine kidney (MDCK) cells were examined. Sequencing analysis revealed substitutions of D190V/N or D225G in the haemagglutinin (HA) proteins in egg isolates, whereas MDCK isolates retained HA genes identical to those of the original viruses presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 39 publications
2
33
0
1
Order By: Relevance
“…Of all HA sequences spanning position 222, close to 92% had 222D, 5.5% had 222E, and 1.4% had 222G, and for 1.3% the amino acid residue at position 222 was uncertain. It has been reported that D222G may arise upon passage of swine influenza A viruses with 222D in embryonated chicken eggs (49). The proportion of sequences with ambiguity at position 222 and sequences with 222G could be related to viral mutants or quasispecies emerging either in vivo or upon propagation in eggs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of all HA sequences spanning position 222, close to 92% had 222D, 5.5% had 222E, and 1.4% had 222G, and for 1.3% the amino acid residue at position 222 was uncertain. It has been reported that D222G may arise upon passage of swine influenza A viruses with 222D in embryonated chicken eggs (49). The proportion of sequences with ambiguity at position 222 and sequences with 222G could be related to viral mutants or quasispecies emerging either in vivo or upon propagation in eggs.…”
Section: Discussionmentioning
confidence: 99%
“…However, D222G in HA is of special interest, since it has also been described as the single change in HA between two strains of the "Spanish" 1918 H1N1 virus that differed in receptor specificity (47). Furthermore, upon propagation in embryonated chicken eggs, pdmH1N1 can acquire the mutation rapidly, presumably because it results in virus adaptation to avian (␣2,3-SAs) receptors (49). The presence of the substitution in pdmH1N1s in the human population and its potential association with more severe disease prompted us to test its effect on pdmH1N1 receptor binding, replication, antigenic properties, and pathogenesis and transmission in animal models.…”
mentioning
confidence: 99%
“…Cytokines and chemokines in the BAL fluid of macaques were measured by using the Milliplex MAP nonhuman primate cytokine/chemokine panel (Millipore, Bedford, MA) with the Bio-Plex 200 system (Bio-Rad Laboratories, Hercules, CA). (11,25,29). All test viruses were generated by using reverse genetics (21) and their genomes completely sequenced to rule out unwanted mutations.…”
Section: Cells and Virusesmentioning
confidence: 99%
“…For example, human H3N2 clinical specimens can be the source of different sequence variants when propagated in MDCK cells or in embryonated eggs (17). Similarly, classical swine H1N1 viruses isolated in eggs have changes at positions 187 and/or 222 and modulate their receptor specificity (4,18).…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic analysis of the 2009 pandemic H1N1 virus (H1N1pdm09) indicated that the genome was a combination of gene segments that had not been previously identified in animal or human influenza viruses (5). The HA gene of H1N1pdm09 belongs to the classical swine lineage distinct from other viruses of human or avian origin that were introduced into pigs more recently, giving rise to 'human-like' and 'avianlike' swine influenza lineages (18). Its ancestry has been traced to the viruses similar to the human pandemic in 1918-1919 (1).…”
Section: Introductionmentioning
confidence: 99%